COVID-19 vaccine acceptance and associated factors among health workers in West Guji zone, Southern Ethiopia: Cross-sectional study - Asefa, Lechisa; Lemma, Hailu; Daba, Chala; Dhengesu, Degefa; Ibrahim, Mommedgezali (Frontiers in Public Health, 2023)
Background Currently, different COVID-19 vaccines are being developed and distributed worldwide to increase the proportion of the vaccinated people and as a result to halt the pandemic. However, the vaccination progress is different from place to place even among health care workers due to variation in vaccine acceptance. Therefore, this study aimed to assess the acceptance of COVID-19 vaccine and determinant factors among healthcare workers in west Guji zone, southern Ethiopia. Method and materials An institutional-based cross-sectional study design was employed to assess COVID-19 vaccine acceptance and associated factors among health care workers from July to August 2021. A simple random sampling technique was used to choose 421 representative healthcare workers from three hospitals in the west Guji Zone. The self-administrated questionnaire was used to collect data. Bivariate and multivariable logistic regression analyses were computed to identify factors associated with the acceptance of the COVID-19 vaccine. P < 0.05 was considered for significantly associated factors. Result From the representative health workers, 57, 47.02, and 57.9% of healthcare workers had good practice of COVID-19 prevention, adequate knowledge, and a positive attitude toward the COVID-19 vaccine consecutively. 38.1% of healthcare workers said they had a willingness to accept the COVI-19 vaccine. Profession (AOR-6, CI: 2.92–8.22), previous history of vaccine side effects (AOR: 3.67, CI: 2.75–11.41), positive attitude toward vaccine acceptance (AOR: 1.38, CI: 1.18–3.29), adequate knowledge toward COVID-19 vaccine (AOR: 3.33, CI: 1.36–8.12), and adequate practice of COVID-19 prevention measure (AOR: 3.45, CI: 1.39–8.61) were significant associated with COVID-19 vaccine acceptance. Conclusion The proportion of COVID-19 vaccine acceptance among health workers was found to be low. From the study variables, profession, previous history of vaccine side effects, positive attitude toward vaccine acceptance, adequate knowledge to ward off COVID-19 vaccine, and adequate practice of COVID-19 prevention measures were significantly associated with COVID-19 vaccine acceptance.